2022
DOI: 10.1155/2022/4775264
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Patients with Cervicofacial Edema and Paresthesia during Perioperative Period of Transoral Endoscopic Thyroidectomy

Abstract: Objective. To analyze the clinical intervention effect of transoral endoscopic thyroidectomy on the neck and face during perioperative period. Method. From January 2019 to January 2020, 60 patients included in this study were randomly divided into observation group and control group according to the ratio of 1 : 1, with 30 cases in each group. Both groups underwent rapid surgical intervention during the perioperative period. The patients in the observation group received neck and face management. The degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Pain is typically localized in the cervical area and various surgical tunnels in different endoscopic approaches. In a study by Yang et al, the VAS scoring was used to assess pain in patients with cervicalofacial edema and paresthesia following transoral endoscopic thyroidectomy [ 38 ]. Several studies have compared postoperative pain levels between endoscopic and open thyroidectomy procedures, as well as different endoscopic approaches, using this pain scale [ 4 , 5 , 20 , 21 , 26 , 31 , 41 , 42 ].…”
Section: Assessment Of Sensory Alterationmentioning
confidence: 99%
See 3 more Smart Citations
“…Pain is typically localized in the cervical area and various surgical tunnels in different endoscopic approaches. In a study by Yang et al, the VAS scoring was used to assess pain in patients with cervicalofacial edema and paresthesia following transoral endoscopic thyroidectomy [ 38 ]. Several studies have compared postoperative pain levels between endoscopic and open thyroidectomy procedures, as well as different endoscopic approaches, using this pain scale [ 4 , 5 , 20 , 21 , 26 , 31 , 41 , 42 ].…”
Section: Assessment Of Sensory Alterationmentioning
confidence: 99%
“…Yang et al and Liang et al conducted assessments of paresthesia in the chin, face, and neck regions of patients who had undergone transoral thyroidectomy using the Semmes–Weinstein monofilament test. The patients were instructed to sit with their eyes closed, after which a nylon filament was applied perpendicularly to the designated area, bent into a C-shape [ 38 , 39 ]. The size of nylon and its representative in the study were as follows: 2.83 = 0.07 g/mm 2 (normal sensation), 3.61 = 0.4 g/mm 2 (hypotactile loss), 4.31 = 2 g/mm 2 (protective hypoesthesia), 4.56 = 4 g/mm 2 (protective loss of sensation), and 5.07 = 10 g/mm 2 (protective loss of sense).…”
Section: Assessment Of Sensory Alterationmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%